Substitution versus redox reactions of gold(III) complexes with L-cysteine, L-methionine and glutathione - Durovic, Mirjana D.; Bugarcic, Zivadin D.; Heinemann, Frank Wilhelm; van Eldik, Rudi (Dalton Transactions, 2014)
The influence of tridentate, nitrogen donor ligands, on the stability of gold(III) complexes under physiological conditions was investigated. The interaction of [Au(terpy)Cl](2+) (terpy = 2,2': 6' 2 '' terpyridine), [Au(bpma)Cl](2+) (bpma = bis(pyridyl-methyl) amine), [Au(dien)Cl](2+) (dien = diethylenetriamine) and [AuCl4](-) with the biologically relevant thiols, L-cysteine (L-Cys) and glutathione (GSH), and thioether, L-methionine (L-Met), was studied using UV-Vis spectroscopy, cyclic voltammetry, H-1 NMR spectroscopy and ESI-MS. In this study, the rate constants for substitution reactions between monofunctional gold(III) complexes and sulfur donor ligands in aqueous solution were determined at different initial concentrations of reactants, chloride ions, pH and constant ionic strength. The obtained second-order rate constants for the reaction with L-methionine in the absence of added chloride at pH 2.5 and 25 degrees C follow the sequence (7.5 +/- 0.4) x 10(3) > (4.5 +/- 0.1) x 10(2) > 88.3 +/- 0.8 M-1 s(-1) for the terpy, bpma and dien complexes, respectively, demonstrating that the substitution step could be detected prior to the reduction step. This behavior was expected due to the influence of a decreasing pi-donor ability of the chelate ligands, which slows down the substitution reactions along the series of complexes studied. In order to throw more light on the mechanism of biological activity of gold(III) compounds, such a systematic study was performed for all the mentioned thiols and thioether.